N-acetylputrescine as a characteristic constituent of cyanelle peptidoglycan in glaucocystophyte algae. - Pfanzagl, B (1996)
Cyanelle peptidoglycan from the glaucocystophyte algae Glaucocystis nostochinearum and Cyanoptyche gloeocystis was investigated by high-performance liquid chromatography of muropeptides, supported by matrix-assisted laser desorption-ionization mass spectrometry. The peptidoglycans of both species are modified with N-acetylputrescine, as has been demonstrated for cyanelle peptidoglycan of Cyanophora paradoxa.